Impacts of Municipal Wastewater on The Transport Characteristics of Reactive Solutes Through Agricultural Soils. Issue 10 (31st May 2019) - Mojid, M. A.; Hossain, A. B. M. Z.; Wyseure, G. C. L.
ABSTRACT: Reliable transport parameters of agrochemicals and soluble pollutants are crucial for modeling and management of soil and groundwater quality. This study investigated impacts of municipal wastewater on the transport parameters of five heavy metal/metalloid compounds (NaAsO2, Cd(NO3 )2, Pb(NO3 )2, Ni(NO3 )2 & ZnCl2 ), two pesticides (cartap & carbendazim) and an inert salt (CaCl2 ) in four agricultural soils of Bangladesh. Solute-breakthrough concentrations were measured in repacked soil columns with time-domain reflectometry (TDR) both before and after wastewater treatment. Transport velocity ( V ), dispersion coefficient ( D ), dispersivity (λ) and retardation factor ( R ) of the solutes, and pertinent soil properties were determined. Wastewater reduced bulk density (γ) of the soils (from 1.32–1.37 g/cm 3 to 1.26–1.35 g/cm 3 ) by increasing organic carbon (OC) (from 0.37%–0.84% to 0.40–0.93%), increased pore-size distribution index ( n ) (by 0.02 unit) and reduced soil pH (from 6.32–7.45 to 5.92–6.46). D and λ decreased while V and R increased after wastewater treatment; D decreased and R increased linearly with decreasing bulk density. The correlations of V, D, and R with n improved significantly (p < 0.05) after wastewater treatment. The correlation between λ and OC improved markedly for Ca, Pb, Ni, and cartap. The observed indicative results have practical implications in developing pedo-transfer functions for solute-transport parameters using basic soil properties, which are subject to progressive modification due to agrochemicals application and wastewater irrigation.